Anticipating innovations in structural biology. (2nd July 2018) - Berman, Helen M.; Lawson, Catherine L.; Vallat, Brinda; Gabanyi, Margaret J.
Abstract: In this review, we describe how the interplay among science, technology and community interests contributed to the evolution of four structural biology data resources. We present the method by which data deposited by scientists are prepared for worldwide distribution, and argue that data archiving in a trusted repository must be an integral part of any scientific investigation.